2012 IEEE Symposium on Security and Privacy 2012
DOI: 10.1109/sp.2012.18
|View full text |Cite
|
Sign up to set email alerts
|

Don't Trust Satellite Phones: A Security Analysis of Two Satphone Standards

Abstract: There is a rich body of work related to the security aspects of cellular mobile phones, in particular with respect to the GSM and UMTS systems. To the best of our knowledge, however, there has been no investigation of the security of satellite phones (abbr. satphones). Even though a niche market compared to the G2 and G3 mobile systems, there are several 100,000 satphone subscribers worldwide. Given the sensitive nature of some of their application domains (e.g., natural disaster areas or military campaigns), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…Driessen et al [31] have recently reverse-engineered the encryption algorithms used in the GMR-1 and GMR-2 satellite phone standards and showed that their stream ciphers are considerably weaker than the current state of the art in symmetric cryptography. They have also developed a mechanism for recovering the encryption key of a GMR-2 phone call with approximately 50-65 bytes of key stream and moderate computational complexity.…”
Section: Satellite Communicationsmentioning
confidence: 99%
“…Driessen et al [31] have recently reverse-engineered the encryption algorithms used in the GMR-1 and GMR-2 satellite phone standards and showed that their stream ciphers are considerably weaker than the current state of the art in symmetric cryptography. They have also developed a mechanism for recovering the encryption key of a GMR-2 phone call with approximately 50-65 bytes of key stream and moderate computational complexity.…”
Section: Satellite Communicationsmentioning
confidence: 99%
“…The four topmost functions in this ranking turned out to implement the different linear feedback shift registers (LFSR) of the cipher . The interested reader is referred to the original publication [Driessen et al 2012] for more details.…”
Section: Finding the Ciphermentioning
confidence: 99%
“…In this paper, we build on our previous work [Driessen et al 2012], which reverseengineered the stream ciphers A5-GMR-1 and A5-GMR-2, used in the respective standards. In contrast to the original publication, we focus less on the process of reverseengineering itself, but rather collect all relevant information regarding security and configuration aspects of the system: We describe the network architecture of satellite telecommunication systems and, to some degree, how they operate on the physical and protocol level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the IoT provides new and exciting experience for end users, it also opens up new avenues to hackers and organized crime. Recent attacks to a wide range of smart devices [12,39] have emphasized that without adequate security the IoT will only become pervasive nightmare.…”
Section: Introductionmentioning
confidence: 99%